EDUCATIONAL STANDARDS AND THE CRISIS OF EDUCATION - D. A. Sevostyanov (Высшее образование в России, 2018)
The article analyzes the problems caused by the implementation of the modern Federal State Educational Standards of higher education. There is no doubt that FSES are necessary to support the educational space throughout the country, to govern the educational activities based on the unified legal framework, to provide, on the one hand, the continuity of the main educational programs, on the other hand, their variability. Meeting the requirements of standards is the condition of education quality assurance. Nevertheless, the current version of FSES has a number of serious conceptual weaknesses that become apparent in the practical application of standards. In particular, it is shown that FSES disregard the hierarchical nature of education. There are disciplines that do not form any competences but they are an essential theoretical basis for studying the other disciplines because there are necessary successive stages in education, e.g. medical or engineering. But this fact is disregarded in the current FSES. On the whole, the system crisis of the national education attended by the educational standards can be overcome through changing the approach to education and the revision of competences formulation in FSES. In this regard, it is important to take into account the specific character of educational activities, the hierarchical nature of education, and also students’ social and psychological qualities, as well as the necessary efforts of teaching staff.